Supporting Nuu-chah-nulth Food Sovereignty by Recentering Indigenous Governance in Sea Otter Management - Popken, Lindsey (2021)
Thesis (Master's)--University of Washington, 2021 Federal sea otter management in Canada faces scrutiny over its ability to adequately address impacts on Indigenous self-determination and food sovereignty. Many Nuu-chah-nulth First Nations maintain that their priorities, interests, and self-determination are undermined and excluded from current sea otter management. This thesis examines resurgence efforts by Nuu-chah-nulth Nations to re-establish ancestral governance through the case study of sea otter management on Vancouver Island. Through a critical synthesis of management reports and interviews with Indigenous and non-Indigenous actors, I consider past, present, and future plans for sea otter management on Vancouver Island through a feminist standpoint analysis. Findings suggest that structural inequities, divergent normative and material priorities, and ontological differences animate a divide between Nuu-chah-nulth and Canadian state governing bodies where it comes to sea otter management practices. Contemporary sea otter governance regimes in Canada are reproducing the unequal power relations of colonialism, to the detriment of social, environmental, legal considerations. I argue that Indigenous resurgence in sea otter management is an enactment of Nuu-chah-nulth food sovereignty, grounded in relationships of reciprocity between all non-humans and Nuu-chah-nulth Nations, and works towards revitalizing ancestral connections with the environment. Therefore, I identify a need to transform the current management system to one rooted in Nuu-chah-nulth knowledge, values, and leadership; such a governance structure would in turn be well-positioned to collaborate with non-Indigenous entities in a system that does not undermine these considerations.